The Impact Of Telemedicine On Global Non-Communicable Disease Management: A Bibliometric And Visualized Analysis: The Impact Of Telemedicine On Global Non-Communicable Disease Management: A Bibliometric And Visualized Analysis - Jumriyanti Nasaru (Jurnal Promosi Kesehatan Poltekkes Bengkulu, 2026)
Background : The global burden of non-communicable diseases (NCDs) continues to escalate, driving the expansion of telemedicine utilization as a transformative and geographically unrestricted healthcare service modality. Objective : This study aimed to comprehensively map the intellectual structure, dominant thematic clusters, and developmental trajectories of global research on telemedicine in NCD management during the period 2022–2025. Methods: An integrative mixed-method approach was employed, combining bibliometric analysis using VOSviewer and Biblioshiny with a Systematic Literature Review (SLR) based on the PRISMA 2020 guidelines. Ten selected articles retrieved from the Scopus and Web of Science databases were included in the analysis. Results: Publication trends demonstrated significant acceleration, with peak scientific productivity recorded in 2024. Five dominant thematic clusters were identified, including: (1) Type 2 Diabetes Mellitus management, (2) cardiorespiratory NCDs, (3) telehealth in primary healthcare services, (4) patient and healthcare provider perspectives, and (5) digital health interventions in low- and middle-income countries (LMICs). Meta-analytic evidence consistently confirmed the effectiveness of telemedicine in reducing HbA1c levels, decreasing hospital readmission rates, and improving the functional capacity of patients with NCDs. Conclusion: Telemedicine has been empirically established as a fundamental component of global NCD management. However, adoption disparities in developing countries and the limited evidence regarding long-term effectiveness remain key priorities for future research agendas.